2020
DOI: 10.1101/2020.09.11.293225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acquisition of Host Cytosolic Protein byToxoplasma gondiiBradyzoites

Abstract: Toxoplasma gondii is a protozoan parasite that persists in the central nervous system as intracellular chronic stage bradyzoites that are encapsulated by a thick cyst wall. While the cyst wall separates bradyzoites from the host cytosol, it has been posited that small solutes can traverse the cyst wall to sustain bradyzoites. Recently it was found that host cytosolic macromolecules can cross the parasitophorous vacuole and are ingested and digested by actively replicating acute stage tachyzoites. However, the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We propose two possibilities, that bradyzoites uptake host proteins that are trafficked to the VAC for degradation via the endolysosomal system or that, in the absence of TgATG9, bradyzoites have an alternative mechanism of autophagy. The first hypothesis is supported by our recent work, which demonstrated that bradyzoites can ingest and degrade host-derived cytosolic proteins (18). In the second possibility, as discussed further below, we observed the formation of vesicles with two or more membranes in ∆atg9 bradyzoites by TEM microscopy and while we are currently unable to determine the nature of these vesicles, it remains possible that they represent alternative autophagosome-like structures that do not stain well with the cationic amphiphilic dye CytoID.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We propose two possibilities, that bradyzoites uptake host proteins that are trafficked to the VAC for degradation via the endolysosomal system or that, in the absence of TgATG9, bradyzoites have an alternative mechanism of autophagy. The first hypothesis is supported by our recent work, which demonstrated that bradyzoites can ingest and degrade host-derived cytosolic proteins (18). In the second possibility, as discussed further below, we observed the formation of vesicles with two or more membranes in ∆atg9 bradyzoites by TEM microscopy and while we are currently unable to determine the nature of these vesicles, it remains possible that they represent alternative autophagosome-like structures that do not stain well with the cationic amphiphilic dye CytoID.…”
Section: Discussionsupporting
confidence: 69%
“…However, this also raises the question as to how T. gondii tissue cysts containing bradyzoites are able to persist within the host with potentially limited access to host material for sustenance. Although recent work reported that T. gondii bradyzoites can ingest and digest protein from the cytosol of infected cells in vitro (18), the extent to which this process helps to sustain bradyzoites remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although host cytosol ingestion has been recently reported to also occur in chronic stage Toxoplasma gondii bradyzoites [ 124 ], the precise role of this pathway in bradyzoite biology remains to be determined. Parasites lacking CPL can differentiate into cysts normally, but eventually accumulate undigested autophagosomes and die [ 125 ].…”
Section: Endocytosis and Endocytic Trafficking In Toxoplmentioning
confidence: 99%